Selected decisions and selected documents of the International Monetary Fund: and selected documents - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1987)
This volume contains decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the IMF, as well as selected documents relating to current activities of the Fund.
Includes index.
oif 11/08/16
Ref.
Keywords: International finance; International Monetary Fund IMF